Taxonomic redescription and biological notes on Diaugia angusta (Diptera,Tachinidae): parasitoid of the palm boring weevils Metamasius ensirostris and M. hemipterus (Coleoptera, Dryophthoridae) - Nihei, Silvio Shigueo; Pavarini, Ronaldo [UNESP] (Pensoft Publishers, 2011)
Diaugia angusta Perty, 1833 is a Neotropical species of Tachinidae (Diptera) reported here as a parasitoid of Metamasius ensirostris (Germar, 1824) and M hemipterus (Linnaeus, 1758) (Coleoptera: Dryophthoridae) in Brazil. Several species of Dryophthoridae and Curculionidae cause damage to bromeliad and palm species, and most are regarded as pests. In the present study, the male and female of D. angusta are morphologically characterized and illustrated to provide a means for the identification of this parasitoid. Data obtained from preliminary field research show that natural parasitism of Metamasius pupae by D. angusta varies by year but can reach nearly 30%. A network of parasitoid-host interactions among tachinid parasitoids and coleopteran hosts reported as bromeliad and palm pests (Dryophthoridae and Curculionidae) in the Americas indicates that the species of the tribe Dexiini sensu lam (including D. angusta) might be promising as biological control agents of these pests.
Keywords: Dexiinae; taxonomy; host record; biological control; palm; bromeliad; Brazil; Neotropical Region